Amino acid polymorphism at residue 222 of the receptor-binding site of the hemagglutinin of the pandemic influenza A(H1N1)pdm09 from patients 166 with lethal virus pneumonia in 2012-2014 - K. G. Krasnoslobodtsev; D. K. Lvov; S. V. Alkhovsky; E. I. Burtseva; I. T. Fedyakina; L. V. Kolobukhina; E. S. Kirillova; S. V. Trushakova; T. A. Oskerko; M. Yu. Shchelkanov; P. G. Deryabin (Вопросы вирусологии, 2016)
Survey data from autopsy specimens from patients who died from pneumonia caused by the influenza A(H1N1) pdm09 in 2012-2014 and mutant forms of influenza virus in these patients (position 222 in the receptor-binding region of hemagglutinin) were presented. In total, according to aggregate data, obtained with three different methods (sequencing, next-generation sequencing (NGS), virus isolation) mutant viruses were detected in 17 (41%) from 41 patients. The proportion of the mutant forms in viral populations ranged from 1% to 69.2%. The most frequent mixture was the wild type (D222) and mutant (D222G), with proportion of mutant type ranged from 3.3% to 69.2% in the viral population. Mutation D222N (from 1.1% to 5.5%) was found rarely. Composition of the viral population from one patient is extremely heterogeneous: in left lung there was only wild type D222, meantime in right lung - mixture of mutant forms 222D/N/G (65.4/32.5/1.1%), in trachea - mixture 222D/G/Y/A (61.8/35.6/1.2/1.4%, respectively), and in bronchi compound of 222D/G/N/A (64.3/33.7/1/1%, respectively) were detected. The obtained data indicate that the process of adaptation of the virus in the lower respiratory tract is coupled with the appearance of different virus variants with mutations in the receptor-binding region. Mutant forms of the virus are observed in the lower respiratory tract of the majority of patients with lethal viral pneumonia. However, if they are a minor part of the population, they cannot be detected by the method of conventional sequencing. They can be identified using the NGS methods.